Discrimination of Phlebotomus perfiliewi transcaucasicus, Ph. major sensu lato and Ph. tobbi (Diptera: Psychodidae) Using Morphometric and DNA Barcoding Methods in the Endemic Foci of Visceral Leishmaniasis in Ardabil Province, North West of Iran - Alireza Barmaki; Yavar Rassi; Azad Absavaran; Amir Ahmad Akhavan; Eslam Moradi-Asl; Alireza Zahraei-Ramazani; Sayena Rafizadeh (Journal of Arthropod-Borne Diseases)
Background: Visceral leishmaniasis, commonly known as kala-azar, and prevalent in more than 70 countries and several regions of Iran. It is one of the main diseases transmitted by sand flies. In this work, geometric morphometrics and DNA barcoding were employed as novel techniques to enhance the diagnostic tools used in this study. Methods: Phlebotomus perfiliewi transcaucasicus, Phlebotomus major s.l., and Phlebotomus tobbi caught from three districts in the Ardabil Province, northwest of Iran. The right wings of 286 female sand flies were analyzed using geometric morphometric (GM) tools. Additionally, the COI gene was isolated from each of the three species, amplified using universal primers, and sequenced through the DNA barcoding method for classification. This sequencing data was then formatted to generate morphometric analyses. Results: The landmarks with the most variations were found in sets 10, 12, 13, and 14, whereas the first set's landmarks at 1 and 11, along with those from the second set at positions 2, 3, and 5 exhibited the greatest variations. Analysis of the size and shape variations in the wings indicates the presence of distinct populations (P< 0.05). Furthermore, the DNA barcoding results not only confirmed the findings from the geometric morphometric analysis but also revealed both interspecific and intraspecific distances. Conclusion: This study was the first attempt to assess whether wing geometry morphometrics, combined with DNA barcode techniques, can effectively distinguish the three mentioned species in the studied areas. Furthermore, the identification of Phlebotomus neglectus in this area prompted recommendations for additional research.